PROXIMATE AND FUEL PROPERTIES OF AFRICAN LOCUST BEAN PULP AND CASSAVA STARCH FLOUR BINDERS FOR FUEL BRIQUETTE PRODUCTION (FUDMA JOURNAL OF SCIENCES, 2024)
The study investigates the proximate and combustion properties of affordable and locally available briquette binders, namely: African locust bean pulp and cassava starch (flour) using the American Society for Testing and Materials (ASTM) methods. The findings indicate varying levels of moisture content (4.55% to 6.89%), volatile matter (30.06% to 64.21%), ash content (0.93% to 23.36%), and fixed carbon (7.89% to 62.12%). Elemental composition of carbon, hydrogen, and oxygen range from 34.24% to 53.25%, 4.39% to 5.09%, and 32.96% to 33.19%, respectively. The calorific values obtained in the study are 16.85±0.48 MJ/kg for African locust bean pulp and 20.69±0.34 MJ/kg for cassava starch flour. Both binders exhibit properties conducive to producing high-quality briquettes capable of generating sufficient heat for household and small-scale industrial settings.
Keywords: African Locust bean pulp; Briquette; Cassava Starch flour; Proximate Analysis; Calorific value